Manufacturing method for inductor-embedded substrate
The method addresses the limitations of using iron oxide fillers by employing a process that forms a magnetic layer and insulating layer on a substrate, allowing for the use of more effective magnetic powders, thereby enhancing inductance in substrates with built-in inductors.
Patent Information
- Application Number
- JP2021140271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-08-30
AI Technical Summary
Existing methods for manufacturing substrates with built-in inductors are limited by the use of iron oxide fillers, which have inferior magnetic properties and are susceptible to deterioration during etching processes.
A manufacturing method that involves filling through holes in a substrate with magnetic paste to form a magnetic layer, then laminating a resin sheet with a metal foil on top, followed by forming a second through hole and creating a plating film or conductive paste within it, allowing for the use of magnetic powders with better magnetic properties like pure iron or iron alloys.
This method enables the production of substrates with built-in inductors using magnetic powders with superior magnetic properties, achieving higher inductance without the limitations of iron oxide fillers.
Smart Images

Figure 0007666240000001 
Figure 0007666240000002 
Figure 0007666240000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a substrate with built-in inductors. [Background technology]
[0002] Inductor-embedded substrates, which incorporate an inductor in a circuit board such as a printed wiring board, are generally formed using a resin composition containing magnetic powder. Known methods for increasing the inductance of the inductor included in the inductor-embedded substrate are to increase the content of magnetic powder in the resin composition or to increase the effective magnetic permeability of the magnetic material, which is a cured product of the resin composition.
[0003] For example, the inductor-embedded component described in Patent Document 1 is described as having a magnetic resin that is filled into an opening in a core substrate and has a second through hole, and a second through-hole conductor made of a metal film formed in the second through hole, the magnetic resin containing iron oxide filler, and a structure in which the magnetic resin and the metal film are in contact with each other. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-86856 Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, a conductor layer is formed on the surface of the magnetic resin by etching, but the magnetic powder contained in the magnetic resin may be eluted or altered by the etching solution used in the etching. For example, when iron filler is used as the magnetic powder, the iron filler may be eluted or altered by the chemical solution, causing the magnetic resin to deteriorate. Therefore, Patent Document 1 uses iron oxide filler as a magnetic powder that is highly resistant to the chemical used in the roughening treatment. However, iron oxide filler has poor magnetic properties such as relative permeability, so it may not be possible to obtain high inductance. Therefore, there has been a demand for a manufacturing method of an inductor-embedded substrate that can use magnetic powder with excellent magnetic properties such as iron filler.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a manufacturing method capable of manufacturing an inductor-embedded substrate using magnetic powder other than iron oxide filler. [Means for solving the problem]
[0007] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that a substrate with an integrated inductor can be manufactured without using iron oxide filler for the magnetic powder contained in the magnetic paste by filling through holes formed in a substrate with a magnetic paste to form a magnetic layer, and then, before forming a second through hole in the magnetic layer, laminating a resin sheet with a metal foil on the substrate so that the resin composition layer is bonded to the substrate, and hardening the resin composition layer to provide an insulating layer, thereby completing the present invention.
[0008] That is, the present invention includes the following. [1] (A) a step of filling a first through-hole of a substrate having first and second main surfaces and penetrating between the first and second main surfaces with a resin composition containing magnetic powder to form a magnetic layer; (B) a step of laminating a resin sheet with a metal foil, which includes a metal foil and a resin composition layer, on a substrate so that the resin composition layer is bonded to the substrate, and curing the resin composition layer to form an insulating layer; and (C) forming a second through hole penetrating the metal foil, the insulating layer, and the magnetic layer, in this order. [2] After step (C), (D-1) forming a plating film in the second through-hole, filling the second through-hole with an insulating paste and hardening the paste; and The method for producing the inductor-embedded substrate according to [1], comprising the step of: (E-1) forming a patterned conductor layer. [3] After step (C), (D-2) filling the second through-hole with a conductive paste and curing it; and The method for producing the inductor-embedded substrate according to [1], comprising the step of: (E-2) forming a patterned conductor layer. [4] The method for producing an inductor-embedded substrate according to any one of [1] to [3], wherein the magnetic powder is at least one type selected from the group consisting of pure iron powder and iron alloy metal powder. [5] The method for producing an inductor-embedded substrate according to any one of [1] to [4], wherein the metal foil includes a copper foil. [6] A method for manufacturing an inductor-embedded substrate according to any one of [1] to [5], comprising the step of forming a first through-hole that penetrates between the first and second main surfaces of the substrate. Effect of the Invention
[0009] According to the present invention, it is possible to provide a manufacturing method capable of manufacturing a substrate with built-in inductors using magnetic powder other than iron oxide filler. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a substrate as an example of a method for manufacturing a circuit substrate according to the first and second embodiments. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a board in which a first through-hole is formed as an example of a method for manufacturing the circuit board according to the first and second embodiments. [Diagram 3]FIG. 3 is a schematic cross-sectional view showing a state of a board in which a magnetic layer is formed in a through-hole as an example of the method for manufacturing the circuit board according to the first and second embodiments. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a state in which a resin sheet with a metal foil is bonded to a substrate as an example of the method for producing a circuit board according to the first and second embodiments. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing a state in which a second through-hole has been formed as an example of the method for manufacturing the circuit board according to the first and second embodiments. [Figure 6] FIG. 6 is a schematic cross-sectional view showing the state of the board after a plating film is formed as an example of the method for manufacturing the circuit board according to the first embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view showing the state of the board after the insulating cured material layer is formed as an example of the method for producing the circuit board according to the first embodiment. [Figure 8] FIG. 8 is a schematic cross-sectional view showing a state of a board on which a conductor layer is formed as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 9] FIG. 9 is a schematic cross-sectional view showing a state of a board on which a pattern conductor layer is formed as an example of the method for manufacturing a circuit board according to the first embodiment. [Figure 10] FIG. 10 is a schematic cross-sectional view showing a state of a board on which a conductive layer has been formed as an example of the method for manufacturing a circuit board according to the second embodiment. [Figure 11] FIG. 11 is a schematic cross-sectional view showing a state of a board on which a conductor layer is formed as an example of the method for manufacturing a circuit board according to the second embodiment. [Figure 12] FIG. 12 is a schematic cross-sectional view showing a state of a board on which a pattern conductor layer is formed as an example of the method for manufacturing a circuit board according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Each drawing merely shows the shape, size, and arrangement of components in a schematic manner to the extent that the invention can be understood. The present invention is not limited by the following description, and each component can be modified as appropriate. In the drawings used in the following description, similar components are indicated by the same reference numerals, and duplicated descriptions may be omitted. Furthermore, the configuration according to the embodiment of the present invention is not necessarily manufactured or used according to the arrangement of the illustrated example.
[0012] The method for manufacturing an inductor-embedded substrate of the present invention includes the steps of: (A) a step of filling a first through-hole of a substrate having first and second main surfaces and penetrating between the first and second main surfaces with a resin composition containing magnetic powder to form a magnetic layer; (B) a step of laminating a resin sheet with a metal foil, which includes a metal foil and a resin composition layer, on a substrate so that the resin composition layer is bonded to the substrate, and curing the resin composition layer to form an insulating layer; and and (C) a step of forming a second through-hole penetrating the metal foil, the insulating layer, and the magnetic layer. The present invention is carried out in the order of steps (A) to (C).
[0013] A first embodiment of the manufacturing method of an inductor-embedded substrate according to the present invention includes the following steps: After step (C), (D-1) forming a plating film in the second through-hole, filling the second through-hole with an insulating paste and hardening the paste; and (E-1) forming a patterned conductor layer.
[0014] In addition, a second embodiment of the method for manufacturing an inductor-embedded substrate according to the present invention includes the following steps: After step (C), (D-2) filling the second through-hole with a conductive paste and curing it; and (E-2) forming a patterned conductor layer.
[0015] If a patterned conductor layer is formed on the magnetic layer by plating, an etching process is required. Since the etching solution used in the etching process may dissolve or alter the magnetic powder, the type of magnetic powder is limited to iron oxide filler.
[0016] In addition, if an insulating layer is formed on a magnetic layer and a patterned conductor layer is formed on the insulating layer, it is required to perform a roughening treatment on the insulating layer before plating in order to improve the adhesion of the patterned conductor layer. However, if the insulating layer is roughened, the chemical solution used for the roughening treatment may enter the second through-hole and come into contact with the magnetic layer, which may cause the magnetic powder to dissolve or deteriorate. Therefore, the type of magnetic powder is limited to iron oxide filler.
[0017] In contrast, according to the manufacturing method of the present invention, after providing an insulating layer and a metal foil on a magnetic layer, a patterned conductor layer can be formed by plating. In this manufacturing method, a patterned conductor layer can be formed on a metal foil. The metal foil and a conductor layer such as a patterned conductor layer formed on the metal foil can be strongly adhered to each other without roughening treatment. Since roughening treatment is not necessary, contact between the magnetic layer and a chemical solution for roughening treatment can be avoided, and the type of magnetic powder is not limited to iron oxide filler. Therefore, an inductor-embedded substrate can be manufactured using a magnetic powder other than iron oxide filler. Since it is possible to use a magnetic powder other than iron oxide filler, a magnetic powder such as an iron filler having better magnetic properties than iron oxide filler can be adopted, and therefore, according to the manufacturing method, it is usually possible to achieve excellent inductance.
[0018] Hereinafter, a method for manufacturing an inductor-embedded substrate according to the first and second embodiments will be described. In the first embodiment, it is preferable to carry out the steps in the order of (A) to (E-1). In the second embodiment, it is preferable to carry out the steps in the order of (A) to (E-2).
[0019] [First embodiment] <Process (A)> In step (A), a magnetic layer is formed by filling a magnetic paste containing magnetic powder into a first through hole of a substrate having first and second main surfaces and penetrating between the first and second main surfaces. The second main surface corresponds to a main surface on the opposite side to the first main surface.
[0020] 1, the step (A) may include a step of preparing a substrate 10 including a support substrate 11, a first metal layer 12 made of a metal such as copper foil provided on both surfaces of the support substrate 11, and a second metal layer 13. Examples of materials for the support substrate 11 include insulating substrates such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. Examples of materials for the first and second metal layers include a carrier-attached copper foil, and a material for the conductor layer described later.
[0021] 2, the method may include a step of forming a first through-hole 14 penetrating between the first and second main surfaces 10a, 10b of the substrate 10. The first through-hole 14 can be formed by, for example, drilling, laser irradiation, plasma irradiation, etc. Specifically, the first through-hole 14 can be formed by forming a through-hole in the substrate 10 using a drill or the like.
[0022] The first through-holes 14 can be formed by using a commercially available drilling device. An example of a commercially available drilling device is "ND-1S211" manufactured by Hitachi Via Mechanics.
[0023] 2 shows a case where there is one first through hole 14, but it is possible to provide a plurality of first through holes 14 at predetermined intervals from each other. By providing a plurality of first through holes 14, it is possible to build a plurality of inductor structures in the substrate 10.
[0024] The opening diameter of the first through-hole 14 is not particularly limited, and may be appropriately determined depending on the specific design of the inductor-embedded substrate to be manufactured. For example, the opening diameter of the first through-hole 14 is preferably 1.0 mm or less, more preferably 0.8 mm or less, from the viewpoint of maintaining the rigidity of the substrate 10. The lower limit is not particularly limited, but is preferably 0.2 mm or more, more preferably 0.25 mm or more, from the viewpoint of the formability of the second through-hole described later.
[0025] The thickness of the substrate 10 is not particularly limited and may be determined according to the specific design of the inductor-embedded substrate to be manufactured. For example, from the viewpoint of improving the inductor performance of the inductor-embedded substrate, the thickness of the substrate 10 is preferably 0.3 μm or more, more preferably 0.5 μm or more, and even more preferably 0.7 μm or more. The upper limit is not particularly limited, but is preferably 2 mm or less, more preferably 1.7 mm or less, and even more preferably 1.5 mm or less.
[0026] After preparing the substrate 10 in which the first through-holes 14 are formed, as shown in an example in Fig. 3, the first through-holes 14 are filled with magnetic paste, and the magnetic paste is thermally cured to form the magnetic layer 20 in the first through-holes 14. Details of the magnetic paste will be described later.
[0027] Methods for filling the magnetic paste include, for example, a method of filling the first through-hole 14 with magnetic paste via a squeegee, a method of filling the magnetic paste via a cartridge, a method of filling the magnetic paste by mask printing, a roll coating method, an inkjet method, etc.
[0028] The thermal curing conditions of the magnetic paste vary depending on the composition and type of the magnetic paste, but the curing temperature is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and preferably 240° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The curing time of the magnetic paste is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 15 minutes or more, and preferably 120 minutes or lower, more preferably 100 minutes or lower, and even more preferably 90 minutes or lower.
[0029] The degree of hardening of the magnetic layer 20 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The degree of hardening can be measured, for example, using a differential scanning calorimeter.
[0030] Before the magnetic paste is thermally cured, the magnetic paste may be subjected to a preheating treatment in which the magnetic paste is heated at a temperature lower than the curing temperature. For example, prior to thermally curing the magnetic paste, the magnetic paste may be preheated at a temperature of usually 50°C or higher and lower than 120°C (preferably 60°C or higher and 110°C or lower, more preferably 70°C or higher and 100°C or lower) for usually 5 minutes or longer (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).
[0031] After forming the magnetic layer 20, if necessary, a step of removing excess magnetic layer 20 protruding from or attached to the substrate 10 by polishing and planarizing the surface may be included. As a polishing method, a method capable of polishing excess magnetic layer 20 protruding from or attached to the substrate 10 can be used. Examples of such polishing methods include buff polishing and belt polishing. An example of a commercially available buff polishing device is "NT-700IM" manufactured by Ishii Hyoki Co., Ltd.
[0032] The arithmetic average roughness (Ra) of the polished surface of the magnetic layer 20 is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the insulating layer described below. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The arithmetic surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0033] -Magnetic paste- The magnetic paste used to form the magnetic layer contains magnetic powder, and may contain a binder resin, a dispersant, a hardening accelerator, and other additives as necessary.
[0034] The magnetic powder is an inorganic filler having a relative magnetic permeability of more than 1, and is preferably at least one selected from pure iron powder and iron alloy metal powder from the viewpoint of improving the magnetic properties of the inductor-embedded substrate. Examples of the iron alloy metal powder include iron alloy metal powders such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Cr-Si alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, and Fe-Ni-Co alloy powder. The iron alloy metal powder preferably includes iron alloy metal powder containing at least one selected from Si, Cr, Al, Ni, and Co.
[0035] As the magnetic powder, commercially available magnetic powders can be used. Specific examples of commercially available magnetic powders include "PST-S" manufactured by Sanyo Special Steel Co., Ltd.; "AW2-08", "AW2-08PF20F", "AW2-08PF10F", "AW2-08PF3F", "Fe-3.5Si-4.5CrPF20F", "Fe-50NiPF20F", "Fe-80Ni-4MoPF20F" manufactured by Epson Atmix; "JR09P2" manufactured by Japan Heavy Chemical Industries Co., Ltd.; "Nanotek" manufactured by CIK Nanotech Co., Ltd.; "JEMK-S" and "JEMK-H" manufactured by Kinsei Matec Co., Ltd.; and "Yttrium iron oxide" manufactured by ALDRICH Co., Ltd. One type of magnetic powder may be used alone, or two or more types may be used in combination.
[0036] The magnetic powder is preferably spherical. The value (aspect ratio) obtained by dividing the length of the long axis of the magnetic powder by the length of the short axis is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1.2 or less. In general, it is easier to improve the relative magnetic permeability when the magnetic powder is flat rather than spherical. However, it is preferable to use spherical magnetic powder, in particular, from the viewpoint of reducing magnetic loss and obtaining a paste having a desired viscosity.
[0037] From the viewpoint of improving the relative magnetic permeability, the average particle size of the magnetic powder is preferably 0.01 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more, and is preferably 10 μm or less, more preferably 9 μm or less, and even more preferably 8 μm or less.
[0038] The average particle size of magnetic powder can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of magnetic powder is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample is preferably magnetic powder dispersed in water using ultrasonic waves. Examples of laser diffraction / scattering type particle size distribution measuring devices that can be used include the "LA-500" manufactured by Horiba, Ltd. and the "SALD-2200" manufactured by Shimadzu Corporation.
[0039] From the viewpoint of improving the relative magnetic permeability, the specific surface area of the magnetic powder is preferably 0.05 m 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more. Also, it is preferably 10m 2 / g or less, more preferably 8m 2 / g or less, more preferably 5m 2 The specific surface area of the magnetic powder can be measured by the BET method.
[0040] From the viewpoint of improving the relative magnetic permeability and reducing the loss factor, the content (volume %) of the magnetic powder is preferably 40% by volume or more, more preferably 50% by volume or more, and even more preferably 60% by volume or more, when the non-volatile components in the magnetic paste are taken as 100% by volume. The upper limit of the content (volume %) is not particularly limited, but may be preferably 95% by volume or less, 90% by volume or less, etc.
[0041] From the viewpoint of improving the relative magnetic permeability and reducing the loss factor, the content (mass%) of the magnetic powder is preferably 70 mass% or more, more preferably 75 mass% or more, and even more preferably 80 mass% or more, when the non-volatile components in the resin composition are taken as 100 mass%. The upper limit of the content (mass%) is not particularly limited, but may be preferably 99 mass% or less, 98 mass% or less, etc.
[0042] There are no particular limitations on the binder resin, so long as it is a resin that can disperse and bind the magnetic powder in the magnetic paste and form a magnetic layer.
[0043] Examples of the binder resin include thermosetting resins such as epoxy resins, phenolic resins, naphthol resins, benzoxazine resins, active ester resins, cyanate ester resins, carbodiimide resins, amine resins, and acid anhydride resins; and thermoplastic resins such as phenoxy resins, acrylic resins, polyvinyl acetal resins, butyral resins, polyimide resins, polyamideimide resins, polyethersulfone resins, and polysulfone resins. As the binder resin, it is preferable to use a thermosetting resin used when forming an insulating layer of a wiring board, and among them, an epoxy resin is preferable. The binder resin may be used alone or in combination of two or more.
[0044] Here, components that react with epoxy resins to harden the magnetic paste, such as phenol-based resins, naphthol-based resins, benzoxazine-based resins, active ester-based resins, cyanate ester-based resins, carbodiimide-based resins, amine-based resins, and acid anhydride-based resins, are sometimes collectively referred to as "curing agents."
[0045] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, the crosslink density of the cured product is sufficient, and a magnetic layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236 and is the mass of a resin containing one equivalent of epoxy groups.
[0046] The weight average molecular weight of the epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0047] When the binder resin contains an epoxy resin and a curing agent, the ratio of the amount of the epoxy resin to all the curing agents is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.5 to 1:3, and even more preferably 1:1 to 1:2, in terms of the ratio of [total number of epoxy groups in the epoxy resin]:[total number of reactive groups in the curing agent]. Here, the "number of epoxy groups in the epoxy resin" refers to the total value of all values obtained by dividing the mass of the non-volatile components of the epoxy resin present in the magnetic paste by the epoxy equivalent. In addition, the "number of active groups in the curing agent" refers to the total value of all values obtained by dividing the mass of the non-volatile components of the curing agent present in the magnetic paste by the active group equivalent.
[0048] From the viewpoint of dispersing and binding the magnetic powder in the magnetic paste and forming a magnetic layer, the content of the binder resin is preferably 1 mass % or more, 3 mass % or more, or 5 mass % or more, and preferably 25 mass % or less, 20 mass % or less, or 15 mass % or less, when the non-volatile components in the magnetic paste are taken as 100 mass %.
[0049] The magnetic paste may further contain a dispersant, which can improve the dispersibility of the magnetic powder.
[0050] Examples of dispersants include phosphate ester-based dispersants such as polyoxyethylene alkyl ether phosphate; anionic dispersants such as sodium dodecyl benzyl sulfonate, sodium laurate, and ammonium salt of polyoxyethylene alkyl ether sulfate; and nonionic dispersants such as organosiloxane-based dispersants, acetylene glycol, polyoxyethylene alkyl ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene alkyl phenyl ether, polyoxyethylene alkyl amine, and polyoxyethylene alkyl amide. Among these, anionic dispersants are preferred. Dispersants may be used alone or in combination of two or more.
[0051] The content of the dispersant is preferably 0.1% by mass or more, 0.2% by mass or more, or 0.4% by mass or more, and the upper limit is preferably 5% by mass or less, 3% by mass or less, or 1% by mass or less, assuming that the non-volatile components in the magnetic paste are 100% by mass.
[0052] The magnetic paste may further contain a curing accelerator. By using the curing accelerator, the curing of the binder resin can be effectively promoted, and the mechanical strength of the cured product can be increased. Examples of the curing accelerator include amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. From the viewpoint of obtaining a magnetic paste with a suitable viscosity, the curing accelerator is preferably an amine-based curing accelerator or an imidazole-based curing accelerator, and more preferably an imidazole-based curing agent. The curing accelerator may be used alone or in combination of two or more kinds.
[0053] From the viewpoint of obtaining a magnetic paste exhibiting an appropriate viscosity, the content of the hardening accelerator is preferably 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more, when the non-volatile components in the magnetic paste are taken as 100% by mass. The upper limit is preferably 3% by mass or less, 2% by mass or less, or 1% by mass or less.
[0054] The magnetic paste may further contain other additives as necessary, such as radical polymerizable compounds, curing retarders such as triethyl borate, flame retardants, thickeners, defoamers, inorganic fillers (excluding magnetic powder), leveling agents, adhesion agents, colorants, and other resin additives.
[0055] The viscosity of the magnetic paste (25°C) is preferably 20 Pa·s or more, more preferably 30 Pa·s or more, and even more preferably 40 Pa·s or more, from the viewpoint of being able to sufficiently fill the first through-holes (and thus be able to form the desired magnetic layer), and is usually 250 Pa·s or less, preferably 220 Pa·s or less, and more preferably 200 Pa·s or less. The viscosity can be measured using an E-type viscometer, keeping the temperature of the magnetic paste at 25±2°C.
[0056] <Process (B)> In step (B), a resin sheet with metal foil, including a metal foil and a resin composition layer, is laminated on a substrate so that the resin composition layer is bonded to the substrate, and the resin composition layer is cured. By curing the resin composition layer, an insulating layer formed by a cured product of the resin composition is obtained. Therefore, an insulating layer and a metal foil are provided in this order on the magnetic layer. The resin sheet with metal foil will be described later.
[0057] In step (B), as shown in an example in Figure 4, a resin sheet 30 with a metal foil, which includes a metal foil 32 and a resin composition layer 31 provided on the metal foil 32, is laminated onto a substrate 10 so that the resin composition layer 31 is bonded to the substrate 10.
[0058] The resin composition layer 31 and the substrate 10 can be joined by, for example, heat-pressing the resin sheet 30 with the metal foil to the substrate 10 from the metal foil 32 side. Examples of a member for heat-pressing the resin sheet 30 with the metal foil to the substrate 10 (hereinafter also referred to as a "heat-pressing member") include a heated metal plate (such as a stainless steel (SUS) plate) or a metal roll (SUS roll). It is preferable to press the resin sheet 30 with the metal foil through a sheet made of an elastic material such as heat-resistant rubber so that the resin sheet 30 with the metal foil can sufficiently follow the irregularities on the surface of the substrate 10, rather than pressing the resin sheet 30 with the heat-pressing member directly in contact with the resin sheet 30 with the metal foil.
[0059] The temperature during thermocompression bonding is preferably in the range of 80°C to 160°C, more preferably 90°C to 140°C, and even more preferably 100°C to 120°C, the pressure during thermocompression bonding is preferably in the range of 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the time during thermocompression bonding is preferably in the range of 20 seconds to 400 seconds, and more preferably 30 seconds to 300 seconds. The joining of the resin sheet with the metal foil to the substrate is preferably carried out under reduced pressure conditions of 26.7hPa or less.
[0060] The resin composition layer 31 of the resin sheet 30 with the metal foil can be bonded to the substrate 10 by a commercially available vacuum laminator. Examples of commercially available vacuum laminators include a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd. and a vacuum applicator manufactured by Nikko Materials Co., Ltd.
[0061] After bonding the resin sheet 30 with the metal foil and the substrate 10, the laminated resin sheet 30 with the metal foil may be smoothed under normal pressure (atmospheric pressure), for example, by pressing the metal foil side with a thermocompression member. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. Note that the lamination and the smoothing treatment may be performed successively using the commercially available vacuum laminator.
[0062] After the resin sheet with the metal foil is laminated on the substrate, the resin composition layer is thermally cured to form an insulating layer.
[0063] The thermal curing conditions of the resin composition layer 31 vary depending on the composition and type of the resin composition layer 31, but the curing temperature is preferably 120° C. or more, more preferably 130° C. or more, even more preferably 150° C. or more, and preferably 240° C. or less, more preferably 220° C. or less, and even more preferably 200° C. or less. The curing time of the resin composition layer 31 is preferably 5 minutes or more, more preferably 10 minutes or more, even more preferably 15 minutes or more, and preferably 120 minutes or less, more preferably 100 minutes or less, and even more preferably 90 minutes or less.
[0064] -Resin sheet with metal foil- The resin sheet with metal foil includes a metal foil and a resin composition layer made of a resin composition provided on the metal foil. The resin composition is preferably one whose cured product has sufficient hardness and insulating properties. Examples of such resin compositions include compositions containing a curable resin and a curing agent thereof. As the curable resin, a conventionally known curable resin used when forming an insulating layer of a printed wiring board can be used, and among them, an epoxy resin is preferable. Therefore, the resin composition includes an epoxy resin and a curing agent. The resin composition may further include an inorganic filler, a curing accelerator, and other additives as necessary.
[0065] (Metal foil) Examples of the metal foil include copper foil and aluminum foil, and copper foil is preferred. The copper foil may be a foil made of a single metal such as copper, or may be a foil made of an alloy of copper and another metal (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0066] The metal foil may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. Examples of multi-layer metal foils include metal foils containing a carrier metal foil and an ultra-thin metal foil bonded to the carrier metal foil. Such multi-layer metal foils may include a release layer between the carrier metal foil and the ultra-thin metal foil that allows the ultra-thin metal foil to be peeled off from the carrier metal foil. The release layer is not particularly limited as long as it can peel off the ultra-thin metal foil from the carrier metal foil, and examples of the release layer include an alloy layer of an element selected from the group consisting of Cr, Ni, Co, Fe, Mo, Ti, W, and P; an organic coating, and the like. When a multi-layer metal foil is used as the support, the resin composition layer is provided on the ultra-thin metal foil.
[0067] From the viewpoint of obtaining the effect of the present invention remarkably, the thickness of the metal foil is preferably 9 μm or more, more preferably 10 μm or more, and even more preferably 11 μm or more. The upper limit is not particularly limited, but is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. The metal foil may have a single layer structure or a multi-layer structure. When the metal foil has a multi-layer structure, it is preferable that the thickness of the entire metal foil is in this range, and the thickness of the ultra-thin metal foil may be, for example, in the range of 0.1 μm to 10 μm.
[0068] The method for producing the metal foil is not particularly limited, but it can be produced by known methods such as electrolysis and rolling.
[0069] (Resin composition) Examples of the epoxy resin include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, glycidylcyclohexane type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, phenolphthalimidine type epoxy resin, and the like. The epoxy resin may be used alone or in combination of two or more kinds.
[0070] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only liquid epoxy resins as the epoxy resins, may contain only solid epoxy resins, or may contain a combination of liquid epoxy resins and solid epoxy resins.
[0071] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, a cured product of the resin composition can be obtained with sufficient crosslink density. The epoxy equivalent is the mass of an epoxy resin containing one equivalent of epoxy groups. This epoxy equivalent can be measured according to JIS K7236.
[0072] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0073] The content of the epoxy resin is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining a cured product exhibiting good mechanical strength and insulation reliability. The upper limit of the content of the epoxy resin is preferably 35% by mass or less, more preferably 30% by mass or less, and particularly preferably 25% by mass or less, based on 100% by mass of the non-volatile components in the resin composition, from the viewpoint of obtaining the desired effects of the present invention significantly.
[0074] Examples of the curing agent include active ester resins, phenol resins, naphthol resins, benzoxazine resins, cyanate ester resins, carbodiimide resins, amine resins, and acid anhydride resins.
[0075] The ratio of the amount of epoxy resin to all curing agents is preferably in the range of 1:0.01 to 1:5, more preferably 1:0.05 to 1:3, and even more preferably 1:0.1 to 1:2, in terms of the ratio of [total number of epoxy groups in epoxy resin] to [total number of reactive groups in curing agent]. Here, the "number of epoxy groups in epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the first resin composition by the epoxy equivalent. In addition, the "number of active groups in curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the curing agent present in the first resin composition by the active group equivalent. By setting the ratio of the amount of epoxy resin to curing agent within this range, a cured product with excellent flexibility can be obtained.
[0076] From the viewpoint of obtaining the effects of the present invention prominently, the content of the curing agent is preferably 1 mass % or more, more preferably 3 mass % or more, and even more preferably 5 mass % or more, relative to 100 mass % of the non-volatile components in the resin composition, and is preferably 15 mass % or less, more preferably 10 mass % or less, and even more preferably 8 mass % or less.
[0077] As the material of the inorganic filler, an inorganic compound is used. Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The inorganic filler may be used alone or in combination of two or more types. The inorganic filler refers to an inorganic filler having a relative magnetic permeability of 1.
[0078] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the inorganic filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, particularly preferably 0.1 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less.
[0079] The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the volume-based particle size distribution of the inorganic filler is measured using a flow cell method, and the average particle size is calculated as the median diameter from the particle size distribution obtained. Examples of laser diffraction particle size distribution measuring devices include the "LA-960" manufactured by Horiba, Ltd. and the "SALD-2200" manufactured by Shimadzu Corporation.
[0080] From the viewpoint of significantly obtaining the desired effects of the present invention, the specific surface area of the inorganic filler is preferably 1 m 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 3m 2 / g or more. There is no particular upper limit, but it is preferably 60m 2 / g or less, 50m 2 / g or less or 40m 2 The specific surface area is measured by using a BET fully automatic specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) to adsorb nitrogen gas onto the surface of the sample, and then calculating the specific surface area using the BET multipoint method.
[0081] In order to improve moisture resistance and dispersibility, the inorganic filler is preferably treated with a surface treatment agent. Examples of the surface treatment agent include fluorine-containing silane coupling agents such as 3,3,3-trifluoropropyltrimethoxysilane; aminosilane coupling agents such as 3-aminopropyltriethoxysilane, N-phenyl-8-aminooctyl-trimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; epoxysilane coupling agents such as 3-glycidoxypropyltrimethoxysilane; mercaptosilane coupling agents such as 3-mercaptopropyltrimethoxysilane; silane coupling agents; alkoxysilanes such as phenyltrimethoxysilane; organosilazane compounds such as hexamethyldisilazane, and titanate coupling agents. The surface treatment agent may be used alone or in any combination of two or more.
[0082] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of the inorganic filler. Specifically, 100 parts by mass of the inorganic filler is preferably surface-treated with 0.2 parts by mass to 5 parts by mass of the surface treatment agent, more preferably 0.2 parts by mass to 3 parts by mass, and even more preferably 0.3 parts by mass to 2 parts by mass.
[0083] From the viewpoint of obtaining the effects of the present invention prominently, the content of the inorganic filler is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more, and is preferably 85% by mass or less, preferably 80% by mass or less, and preferably 75% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass.
[0084] The hardening accelerator and other additives are the same as those that may be contained in the magnetic paste.
[0085] The resin sheet with metal foil can be produced, for example, by preparing a resin varnish by dissolving a resin composition in an organic solvent, applying this resin varnish onto a metal foil using a die coater or the like, and then drying the resin varnish to form a resin composition layer.
[0086] From the viewpoint of obtaining the effects of the present invention remarkably, the thickness of the resin composition layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The upper limit is not particularly limited, but is preferably 50 μm or less, more preferably 45 μm or less, and even more preferably 40 μm or less.
[0087] Examples of organic solvents include ketones such as methyl ethyl ketone (MEK) and cyclohexanone, aromatic hydrocarbons such as xylene and tetramethylbenzene, glycol ethers such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether, esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, carbitol acetate, and ethyl diglycol acetate, aliphatic hydrocarbons such as octane and decane, and petroleum solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. These may be used alone or in combination of two or more.
[0088] <Process (C)> 5, a second through-hole 21 is formed penetrating the metal foil 32, the insulating layer 31a, and the magnetic layer 20. The second through-hole 21 can be formed by the same method as the first through-hole 14.
[0089] The opening diameter of second through hole 21 is not particularly limited as long as it is smaller than the opening diameter of first through hole 14, and may be appropriately determined according to the specific design of the inductor-embedded substrate to be manufactured. For example, from the viewpoint of improving the inductor performance, the opening diameter of second through hole 21 is preferably 0.4 mm or less, more preferably 0.3 mm or less. There is no particular lower limit, but from the viewpoint of the formability of the second through hole, it is preferably 0.05 mm or more, more preferably 0.1 mm or more.
[0090] After the second through-holes are formed, a water washing step may be carried out to remove smears (processing residues) in the second through-holes.
[0091] The water washing is preferably carried out under high pressure. The pressure in the water washing is preferably 1 MPa or more, more preferably 1.5 MPa or more, and even more preferably 2 MPa or more, and is preferably 10 MPa or less, more preferably 8 MPa or less, and even more preferably 5 MPa or less.
[0092] The time for washing with water is preferably 1 second or more, more preferably 5 seconds or more, and even more preferably 10 seconds or more, and is preferably 60 seconds or less, more preferably 30 seconds or less, and even more preferably 20 seconds or less.
[0093] <Process (D-1)> In the first embodiment, after the step (C), a step (D-1) is performed. In the step (D-1), a plating film is formed in the second through-hole, and an insulating paste is filled in the second through-hole with the plating film formed therein and then cured.
[0094] In step (D-1), first, a plating film 40 is formed in the second through-hole 21, as shown in an example in FIG. In the step of forming the plating film 40 in the second through-hole 21, the plating film 40 may also be formed on portions of the substrate 10 other than the second through-hole 21. The plating film 40 is formed by a plating method. Preferred embodiments of the plating method include a semi-additive method and a full-additive method.
[0095] From the viewpoint of thinning, the thickness of the plating film 40 is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0096] After the plating film 40 is formed, as shown in an example in FIG. 7, the second through-hole 21 in which the plating film 40 is formed is filled with an insulating paste, and the insulating paste is cured to form an insulating cured material layer 50.
[0097] Methods for filling the insulating paste include, for example, a method of filling the insulating paste into the second through-hole 21 via a squeegee, a method of filling the insulating paste via a cartridge, a method of filling the insulating paste by mask printing, a roll coating method, an inkjet method, etc.
[0098] The thermal curing conditions for the insulating paste may be the same as the thermal curing conditions for the resin composition layer of the resin sheet with the metal foil.
[0099] The insulating paste contains an epoxy resin and a curing agent, and may further contain an inorganic filler, a curing accelerator, and other additives as necessary. The epoxy resin, the curing agent, the inorganic filler, the curing accelerator, and other additives are as described above. The insulating paste may have the same composition as the resin composition, or may have a different composition.
[0100] After forming the insulating cured material layer 50, if necessary, a step of removing excess insulating cured material layer 50 protruding from or adhering to the substrate 10 by polishing to flatten the layer may be included. The polishing method is as described above.
[0101] After the insulating cured material layer 50 is formed, the surface of the insulating cured material layer 50 may be roughened. The surface of the insulating cured material layer 50 may be polished, and then the polished surface of the insulating cured material layer 50 may be roughened. The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order. The method of polishing the insulating cured material layer is as described above.
[0102] <Process (E-1)> In step (E-1), a patterned conductor layer is formed. In detail, as shown in an example in Fig. 8, a conductor layer 60 is formed on the insulating cured material layer 50, the plating film 40, and the metal foil 32. After the conductor layer 60 is formed, a part of the conductor layer 60 is removed by a process such as etching to form a patterned conductor layer 61, as shown in an example in Fig. 9. When removing the part of the patterned conductor layer 61, the plating film 40 and the metal foil 32 may also be removed in part, if necessary.
[0103] The method for forming the conductor layer 60 includes, for example, plating, sputtering, vapor deposition, etc., among which plating is preferred. In a preferred embodiment, the surface of the cured product is plated by an appropriate method such as a semi-additive method or a full-additive method to form a patterned conductor layer having a desired wiring pattern. Examples of materials for the conductor layer include single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium; and alloys of two or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among these, from the viewpoints of versatility, cost, ease of patterning, etc., it is preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy, and it is more preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, and it is even more preferable to use copper.
[0104] Here, an example of an embodiment in which the patterned conductor layer 61 is formed will be described in detail. A plating seed layer (not shown) is formed on the surfaces of the insulating cured material layer 50, the plating film 40, and the metal foil 32 by electroless plating. Next, an electrolytic plating layer is formed on the formed plating seed layer by electrolytic plating to form the conductor layer 60. After forming the conductor layer 60, unnecessary plating film 40, metal foil 32, plating seed layer, etc. can be removed by etching or other treatment to form a conductor layer having a desired wiring pattern. After forming the patterned conductor layer, an annealing treatment may be performed as necessary for the purpose of improving the peel strength of the conductor layer, etc. The annealing treatment can be performed, for example, by heating the circuit board at 150 to 200°C for 20 to 90 minutes.
[0105] From the viewpoint of thinning, the thickness of the patterned conductor layer is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.
[0106] [Second embodiment] Step (A) in the second embodiment is the same as step (A) in the first embodiment.
[0107] Step (B) in the second embodiment is the same as step (B) in the first embodiment.
[0108] Step (C) in the second embodiment is the same as step (C) in the first embodiment.
[0109] <Process (D-2)> In the second embodiment, after step (C), step (D-2) is performed. In step (D-2), the second through-hole is filled with a conductive paste and hardened. In detail, after the second through-hole 21 is formed, the second through-hole is filled with a conductive paste and hardened to form a conductive layer 70, as shown in an example in FIG. 10.
[0110] Methods for filling the conductive paste include, for example, a method of filling the second through-hole 21 with the conductive paste via a squeegee, a method of filling the conductive paste via a cartridge, a method of filling the conductive paste by mask printing, a roll coating method, an inkjet method, etc.
[0111] The thermal curing conditions for the conductive paste may be the same as the thermal curing conditions for the magnetic paste.
[0112] -Conductive paste- The conductive paste contains a conductive filler, and may contain a binder resin, a hardening accelerator, and other additives as necessary. The binder resin, the hardening accelerator, and other additives are as described above.
[0113] The conductive filler is at least one selected from metal particles selected from silver, copper, and nickel, and metal-coated particles coated with a metal selected from silver, copper, and nickel. Examples of the metal particles include silver particles, copper particles, and nickel particles. Examples of the metal-coated particles include metal-coated metal particles in which metal particles are coated with a metal, and metal-coated resin particles in which resin particles such as polyamide and polybenzoguanamine are coated with a metal. Examples of the metal-coated particles include silver-coated particles such as silver-coated metal particles and silver-coated resin particles; copper-coated particles such as copper-coated metal particles and copper-coated resin particles; nickel-coated particles such as nickel-coated metal particles and nickel-coated resin particles; and the like.
[0114] The conductive filler preferably has a flake (scale) or filament (dendritic) shape. The conductive filler may be used alone or in combination of two or more kinds.
[0115] From the viewpoint of film-forming property and conductivity, the average particle size of the conductive filler is preferably 50 μm or less, more preferably 35 μm or less, even more preferably 20 μm or less, and even more preferably 10 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 0.001 μm or more, more preferably 0.005 μm or more, and even more preferably 0.01 μm or more. The average particle size of the conductive filler can be measured by the same method as the average particle size of the magnetic powder.
[0116] From the viewpoint of improving moisture resistance and dispersibility, the conductive filler is preferably treated with one or more surface treatment agents such as a silane-based surface treatment agent, such as an aminosilane-based coupling agent, an epoxysilane-based coupling agent, a mercaptosilane-based coupling agent, a silane-based coupling agent, an alkoxysilane compound, an organosilazane compound, or a titanate-based coupling agent; a polyester-based dispersant; or the like.
[0117] From the viewpoint of obtaining a conductive layer with low resistance, the content of the conductive filler is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more, when the non-volatile components in the conductive paste are taken as 100% by mass. From the viewpoint of adhesiveness of the conductive layer, the upper limit of the content of the conductive filler in the conductive paste is preferably 98% by mass or less, more preferably 95% by mass or less.
[0118] After the conductive layer 70 is formed, the conductive layer 70 may be polished, or the surface of the conductive layer 70 may be roughened, if necessary.
[0119] <Process (E-2)> In step (E-2), a patterned conductor layer is formed. In detail, as shown in FIG. 11, a conductor layer 60 is formed on a conductive layer 70 and a metal foil 32. After the conductor layer 60 is formed, a part of the conductor layer 60 is removed by a process such as etching to form a patterned conductor layer 61, as shown in FIG. 12.
[0120] The step (E-2) in the second embodiment can be carried out in the same manner as the step (E-1) in the first embodiment.
[0121] The inductor-embedded substrate obtained by the manufacturing method according to the first and second embodiments can be used as a wiring board for mounting electronic components such as semiconductor chips, and can also be used as a (multilayer) printed wiring board using such a wiring board as an inner layer substrate. Moreover, such a wiring board can also be used as an individualized chip inductor component, and can also be used as a printed wiring board with the chip inductor component surface-mounted.
[0122] In addition, various types of semiconductor devices can be manufactured using such a wiring board. The semiconductor device including such a wiring board can be suitably used in electric products (e.g., computers, mobile phones, digital cameras, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES
[0123] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0124] [Example of the first embodiment] <Process (A)> An inner layer board ("MCL-E-705GL", copper foil etched out product, manufactured by Hitachi Chemical Co., Ltd.) with a thickness of 0.8 mm was prepared. A first through hole was formed in this inner layer board with a drill. The first through hole was formed using a drill "ST" manufactured by Union Tool Co., Ltd.
[0125] A magnetic paste containing an iron alloy filler as a magnetic powder was vacuum printed into the first through-hole. The magnetic paste used had a magnetic powder content of 90% by mass, a viscosity of 60 Pa·sec (measurement environment: E-type viscometer, 25°C, 5 rpm), and a relative permeability (100 MHz) of 7. After vacuum printing, the magnetic paste was thermally cured by heating at 150°C for 30 minutes to provide a magnetic layer inside the first through-hole. Next, the surfaces of the inner layer substrate and the magnetic layer were polished and smoothed. Polishing was performed using a ceramic polishing roll #1500 manufactured by Ishii Hyoki Co., Ltd.
[0126] <Process (B)> Next, a resin sheet with metal foil (manufactured by Ajinomoto Fine-Techno Co., Ltd., "ABF-GX92-RCC", resin composition layer thickness 30 μm, support copper foil) was laminated by vacuum lamination on both sides of the inner layer substrate so that the resin composition layer was bonded to the surface of the inner layer substrate. After vacuum lamination, the resin composition layer was thermally cured by heating at 100° C. for 30 minutes and then at 180° C. for 30 minutes to obtain an insulating layer.
[0127] <Process (C)> Second through holes with a smaller diameter than the first through holes were formed in the copper foil support, the insulating layer, and the magnetic layer using a drill "NEU" manufactured by Union Tool Co., Ltd. After the second through holes were formed, processing residues from the formation of the second through holes were removed by high-pressure water washing.
[0128] <Process (D-1)> After removing processing residues by high-pressure water washing, electroless plating was performed in each second through-hole to a thickness of 0.7 μm, and then electrolytic plating was performed to a thickness of 22 μm to form a plating film in the second through-hole.
[0129] After the plating film was formed, an insulating hole-filling paste ("IR-10F", manufactured by San-ei Chemical Co., Ltd.) was vacuum-printed into the second through-hole. After the vacuum printing, the plate was heated at 110°C for 30 minutes, and then heated at 150°C for 60 minutes to thermally cure the insulating hole-filling paste and provide an insulating cured material layer. The surface of the insulating cured material layer was then polished and smoothed. The polishing was performed using a ceramic polishing roll #1500 manufactured by Ishii Hyoki Co., Ltd.
[0130] <Process (E-1)> After polishing the surface of the insulating cured material layer, the insulating cured material layer was subjected to a surface roughening treatment. The polished surface of the insulating cured material layer was subjected to electroless plating to a thickness of 0.7 μm. Then, electrolytic plating was applied to a thickness of 22 μm to form a conductor layer together with the plating film.
[0131] A dry film was laminated on the conductor layer, exposed to light, developed, and patterned. Next, a patterned conductor layer was formed by a subtractive method using an iron chloride etching solution, and then the dry film was peeled off to produce an inductor-embedded substrate.
[0132] [Example of the second embodiment] <Process (A)> An inner layer board ("MCL-E-705GL", copper foil etched out product, manufactured by Hitachi Chemical Co., Ltd.) with a thickness of 0.8 mm was prepared. A first through hole was formed in this inner layer board with a drill. The first through hole was formed using a drill "ST" manufactured by Union Tool Co., Ltd.
[0133] A magnetic paste was vacuum printed into the first through-hole. The magnetic paste used had a magnetic powder content of 90% by mass, a viscosity of 60 Pa·sec (measurement environment: E-type viscometer, 25°C, 5 rpm), and a relative magnetic permeability (100 MHz) of 7. After vacuum printing, the magnetic paste was thermally cured by heating at 150°C for 30 minutes to provide a magnetic layer inside the first through-hole. Next, the surfaces of the inner layer substrate and the magnetic layer were polished and smoothed. Polishing was performed using a ceramic polishing roll #1500 manufactured by Ishii Hyoki Co., Ltd.
[0134] <Process (B)> Next, a resin sheet with metal foil (manufactured by Ajinomoto Fine-Techno Co., Ltd., "ABF-GX92-RCC", resin composition layer thickness 30 μm, support copper foil) was laminated by vacuum lamination on both sides of the inner layer substrate so that the resin composition layer was bonded to the surface of the inner layer substrate. After vacuum lamination, the resin composition layer was thermally cured by heating at 100° C. for 30 minutes and then at 180° C. for 30 minutes to obtain an insulating layer.
[0135] <Process (C)> Second through holes with a smaller diameter than the first through holes were formed in the copper foil support, the insulating layer, and the magnetic layer using a drill "NEU" manufactured by Union Tool Co., Ltd. After the second through holes were formed, processing residues from the formation of the second through holes were removed by high-pressure water washing.
[0136] <Process (D-2)> After removing processing residues by high-pressure water washing, a conductive hole-filling paste ("AE2217", manufactured by Tatsuta Electric Wire Co., Ltd.) was vacuum-printed into the second through-hole. After vacuum printing, the conductive hole-filling paste was thermally cured by heating at 60°C for 30 minutes and then at 160°C for 60 minutes, providing a conductive layer in the second through-hole. The surface of the conductive layer was then polished and smoothed. Polishing was performed using a ceramic polishing roll #1500 manufactured by Ishii Hyoki Co., Ltd.
[0137] <Process (E-2)> The inner layer substrate surface and the conductive layer surface were electrolytically plated to a thickness of 22 μm to form a conductor layer together with the supporting copper foil.
[0138] A dry film was laminated on the conductor layer, exposed to light, developed, and patterned. Next, a patterned conductor layer was formed by a subtractive method using an iron chloride etching solution, and then the dry film was peeled off to produce an inductor-embedded substrate. [Explanation of symbols]
[0139] 10 Substrate 10a First main surface 10b Second main surface 11 Support substrate 12 1st metal layer 13 Second metal layer 14 First through hole 20 Magnetic layer 20 Plating layer 21 Second through hole 30 Resin sheet with metal foil 31 Resin composition layer 31a Insulating layer 32 Metal foil 40 Plating film 50 Insulating hardened layer 60 Conductor Layer 61 Patterned conductor layer 70 Conductive Layer
Claims
1. (A) a step of filling a first through-hole of a substrate having first and second main surfaces and penetrating between the first and second main surfaces with a resin composition containing magnetic powder to form a magnetic layer; (B) laminating a metal foil-attached resin sheet including a metal foil and a resin composition layer on a substrate such that the resin composition layer is bonded to the substrate, and curing the resin composition layer to form an insulating layer; and (C) forming a second through hole penetrating the metal foil, the insulating layer, and the magnetic layer, in this order, A method for producing a substrate with a built-in inductor, wherein the magnetic powder is at least one type selected from the group consisting of pure iron powder and iron alloy metal powder.
2. The method for manufacturing a substrate with an inductor built in according to claim 1 , wherein the second through hole is formed in the metal foil, the insulating layer and the magnetic layer.
3. 3. The method for producing an inductor-embedded substrate according to claim 1, wherein the step (A) includes a step of flattening the magnetic layer.
4. 4. The method for manufacturing an inductor-embedded substrate according to claim 1, wherein the step (B) is carried out immediately after the step (A).
5. After step (C), (D-1) forming a plating film in the second through hole, filling the second through hole with an insulating paste and hardening the paste; and 5. The method for producing the inductor-embedded substrate according to claim 1, further comprising: (E-1) a step of forming a pattern conductor layer.
6. After step (C), (D-2) filling the second through-holes with a conductive paste and hardening the paste; and The method for producing the inductor-embedded substrate according to any one of claims 1 to 4, further comprising: (E-2) a step of forming a pattern conductor layer.
7. 7. The method for producing a substrate with built-in inductor according to claim 1, wherein the metal foil includes a copper foil.
8. 8. The method for manufacturing an inductor-embedded substrate according to claim 1, further comprising the step of forming a first through-hole that penetrates between the first and second main surfaces of the substrate.
Citation Information
Patent Citations
Wiring board and manufacturing method of the same
JP2013008895A
Wiring board having inductor function and method for manufacturing the same
JP2021061264A
Inductor built-in board and manufacturing method thereof
JP2021086856A
Inductor built-in substrate and manufacturing method thereof
JP2021097130A
Thin film barrier seed matallization in magnetic-plugged through hole inductor
US20190279806A1